CONSUMPTION TREND OF OPIOIDS IN AMBULATORY PATIENTS IN ALBANIA 2014-2019 - KAKARIQI, LAERTA; XHAXHO, SOKRAT; DEDA, LEONARD; VYSHKA, GENTIAN (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The aim of this paper is to evaluate 6‐year trends in community use of prescribed opioid analgesics in Albania, using the Anatomic Therapeutic Chemical Classification-Defined Daily Dose methodology. Methods: We collected the data from the database of the Health Insurance Institute (HII). Analysis of the data includes the period 2014–2019; also, we analyzed the data of import and domestic production of drugs, which represent the real consumption of drugs in the country. These data were subsequently involved in a comparative analysis of the utilization data according to the HII. Results: We report a 2.5 fold increase in opioid utilization over the study period. The maximal rise in consumption refers to fentanyl, oxycodone, and tramadol. Meanwhile, the maximal values of consumption refer to strong opiate, morphine. We note that around 30% of the consumption of this class flows out of the scheme. Furthermore, around 25% of consumption of morphine and oxycodone flows out of scheme too. Meanwhile, the tramadol consumption runs out of the scheme over 200%. Conclusions: The outcomes indicate that patients in Albania have low access to opioids medications mainly because of low opioids availability. A strong opiophobia among the population and the medical professionals constitutes one of the major impediments for efficient palliative care.